Differences in Immunoglobin a Levels in Breast Milk Between Mothers with and without the Covid 19 Vaccine - Atika Fadhilah Danaz Nasution; Imelda (Utan Kayu Publishing, 2022)
Giving the vaccine to breastfeeding mothers will provide immunity to the baby through the placenta, umbilical cord (IgG) and breast milk (IgA). The purpose of this study was to analyze differences in IgA levels in breast milk in breastfeeding mothers with the Covid 19 vaccine and without the Covid 19 vaccine. This study used an observational comparative analytic study in 2 unpaired groups with a cross sectional design. The research sites for taking breast milk were in the Working Area of ??Paal Merah I Public Health Center, Jambi City, PMB Rosmala Aini and the Biomedical Laboratory of the Faculty of Medicine, Andalas University for the assessment of breast milk IgA levels. The population in this study were all breastfeeding mothers who had received the Covid-19 vaccine stage 1 and stage 2 and as controls were all breastfeeding mothers who had not received the Covid-19 vaccine in the Paal Merah I Health Center Work Area and PMB Rosmala Aini Jambi City. a sample of 40 respondents. In the univariate analysis, the normality of the data was tested first using Shapiro Wilk. In Bivariate analysis to see the difference in IgA levels with unpaired t test if the data is normally distributed (p value> 0.05), if the data is not normally distributed (p value 0.05) an alternative test is used, namely Mann Whitney. The results showed that the average level of Immunoglobin A in breastfeeding mothers with the Covid-19 vaccine was 2.30 ± 0.44 ng/ml, while the average level of Immunoglobin A in breastfeeding mothers without the Covid-19 vaccine was 2.54 ± 0.45 ng. /ml. The results of the independent t test found that the P-value was 0.10, so it can be concluded that there is no difference in the levels of Immunoglobin A in breast milk between breastfeeding mothers with the Covid-19 vaccine and without the Covid-19 vaccine. The conclusion of the study is that there is no difference in levels of Immunoglobin A in breast milk both in breastfeeding mothers with the Covid-19 vaccine and without the Covid-19 vaccine. Abstrak: Pemberian vaksin pada ibu menyusui akan memberikan kekebalan pada bayi melalui plasenta, tali pusat (IgG) dan ASI (IgA). Tujuan penelitian adalah menganalisis perbedaan kadar Ig A ASI pada Ibu Menyusui dengan vaksin Covid 19 dan tanpa vaksi Covid 19. Penelitian ini menggunakan jenis penelitian analitik komparatif observasional pada 2 kelompok tidak berpasangan dengan desain cross sectional. Tempat penelitian pengambilan ASI Ibu di Wilayah Kerja Puskesmas Paal Merah I Kota Jambi, PMB Rosmala Aini dan Laboratorium Biomedik Fakultas Kedokteran Universitas Andalas untuk penilaian kadar IgA ASI. Populasi pada penelitian ini adalah seluruh ibu menyusui yang telah mendapat vaksin Covid-19 tahap 1 dan tahap 2 dan sebagai kontrol adalah seluruh ibu menyusui yang belum mendapat vaksin Covid-19 di Wilayah Kerja Puskesmas Paal Merah I dan PMB Rosmala Aini Kota Jambi, dengan jumlah sampel sebanyak 40 responden. Pada analisis univariat dilakukan uji normalitas data terlebih dahulu menggunakan shapiro wilk. Pada analisis Bivariat untuk melihat perbedaan kadar Ig A dengan uji t tidak berpasangan jika data berdistribusi normal (nilai p>0,05), jika data tidak berdistribusi normal (nilai p?0,05) digunakan uji alternatif yaitu mann whitney. Hasil penelitian menunjukkan bahwa rerata kadar Immunoglobin A pada ibu menyusui dengan vaksin covid-19 adalah 2,30 ± 0,44 ng/ml, sedangkan rerata kadar Immunoglobin A pada ibu menyusui tanpa vaksin Covid-19 adalah 2,54 ± 0,45 ng/ml. hasil uji independen t test ditemukan bahwa nilai P-value 0,10 sehingga dapat disimpulkan tidak terdapat perbedaan Kadar Immunoglobin A pada ASI antara ibu menyusui dengan Vaksin Covid-19 dan tanpa Vaksin Covid-19. Kesimpulan penelitian bahwa tidak berbeda kadar Immunoglobin A pada ASI baik pada ibu menyusui dengan Vaksin Covid-19 dan tanpa Vaksin Covid-19